2014
DOI: 10.1103/physreva.89.053414
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-resolved above-threshold ionization of xenon with short laser pulses

Abstract: We present intensity-resolved above threshold ionization (ATI) spectra of xenon using an intensity scanning and deconvolution technique. Experimental data were obtained with laser pulses of 58 fs and central wavelength of 800 nm from a chirped-pulse amplifier. Applying a deconvolution algorithm, we obtained spectra that have higher contrast and are in excellent agreement with characteristic 2 and 10 p U cutoff energies contrary to that found for raw data.The retrieved electron ionization probability is consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Details of our experimental equipment have been described previously [8]. Briefly, our Ti:sapphire laser system produced 57 fs pulses with a center wavelength of 800 nm.…”
mentioning
confidence: 99%
“…Details of our experimental equipment have been described previously [8]. Briefly, our Ti:sapphire laser system produced 57 fs pulses with a center wavelength of 800 nm.…”
mentioning
confidence: 99%
“…It is shown that the intensity-resolved energy and momentum spectra offer a wealth of information about the formation of the ATI. Actually, the intensity-resolved energy or momentum spectrum has been used to investigate the underlying dynamics of single ionization [14,[16][17][18], double ionization [19], and high-order harmonic generation [20]. For single ionization, the intensity-resolved energy spectrum has only studied at comparably large intensities (larger than 3×10 13 W/cm 2 for Xe and larger than 1×10 14 W/cm 2 for H) [14,16,17], at which the nonresonant ionization has a significant contribution.…”
mentioning
confidence: 99%
“…Actually, the intensity-resolved energy or momentum spectrum has been used to investigate the underlying dynamics of single ionization [14,[16][17][18], double ionization [19], and high-order harmonic generation [20]. For single ionization, the intensity-resolved energy spectrum has only studied at comparably large intensities (larger than 3×10 13 W/cm 2 for Xe and larger than 1×10 14 W/cm 2 for H) [14,16,17], at which the nonresonant ionization has a significant contribution. Decreasing the laser intensity, the relative contribution of the nonresonant multiphoton ionization decreases [21].…”
mentioning
confidence: 99%
“…Vast theoretical and experimental efforts are focused on, e.g. the determination of intensity-dependent ionization probabilities [1,2] and cut-off energies for direct and rescattered electrons [2], the recognition of Freeman resonances [3][4][5], the observation of channel-switching and -closing effects [6,7], and the analysis of the photoelectron orbital angular momentum [5,7] in the multi-photon regime as well as the imaging of the initial stateʼs electron density distribution [8][9][10].…”
Section: Introductionmentioning
confidence: 99%